Exploring distance in leader-follower relationships : when near is far and far is near - Bligh, Michelle C.; Riggio, Ronald E. (New York : Routledge, 2013)
'Leaders face new challenges as they cope with changes in culture, technology and the workplace. In this edited volume, based on a conference at Claremont, scholars of leadership studies from three continents discuss the latest psychological research on interpersonal leader--follower relations. The book tackles the impact of distance -- physical, interpersonal and social -- on our organizations, governments and societies.'--Publisher's website.
Part I: Foundations and Definitions of Distance. Foundation of Distance / Lisk, Lewandowski ; Notes on Distance and Leadership / Shamir. -- Part 2: The Impact of Distance on Leader-Follower Relations. Leading in a Digital Age: What's Different, Issues Raised, And What We Know / Kahai ; Engaging Followers At a Distance: Leadership Approaches That Work / Reichard, Serrano, Wefald ; The Role of Distance in Leader-Member Exchange (LMX) / Schyns ; The Far Side of Leadership: Rather Difficult to Face / Antonakis, Jacquart. -- Part 3: Moving Forward Emerging Concepts and Extensions of Leader-Follower Distance. Women as Leaders: Paths Through the Labyrinth / Eagly ; The Tyranny of Normative Distance: A Social Identity Account of the Exercise of Power by Remote Leaders / Rast, Gaffney, Hogg ; The Apple Does Not Fall Far From the Tree: Steve Jobs's Leadership as Simultaneously Distant and Close / Razin, Kark ; American Presidential Leadership: Leader Credit, Follower Inclusion, and Obama's Turn / Hollander.
Includes bibliographical references and indexes.
Keywords: Leadership -- Psychological aspects